Estimation of rainfall erosivity (R) using Geo-spatial technique for the state of Tripura, India: A comparative study - DAS, SUSANTA; DAS, RANJIT; BORA, PRADIP KUMAR; OLANIYA, MANISH (The Indian Journal of Agricultural Sciences, 2022)
The principal-agent of soil detachment is rainfall kinetic energy (KE), which must be assessed to understand the nature of erosion, particularly in high rainfall regions, and is designated as a rainfall erosivity index (R). The present study aimed to develop and choose an appropriate model for estimating the R factor in the Indian state of Tripura. The study employed the following three models: KE>25 index model, average annual rainfall model, and monthly and average annual rainfall model. The rainfall data were collected from MOSDAC and https://www. worldweatheronline.com for the calculation of point R-value. The interpolation technique (Kriging) in the ArcGIS environment was adopted to find the spatial variation of the rainfall and R factor over the region. The average annual R factor of the study area was 1089.89, 533.17, and 2452.27 MJ mm/ha/h/y as calculated by Model-1, Model-2, and Model-3, respectively, for the study period (2008–17). The results show that Tripura has high rainfall erosivity which may lead to soil erosion. The comparative analysis shows Model-2 has underestimated approximately 70% whereas Model-3 has overestimated about 15% of the R factor values by considering Model-1 as base. The results demonstrate that Model-2 can be used as an alternative for estimation of rainfall erosivity in an area where the daily rainfall data is not available. These findings may help researchers to select a suitable method for the calculation of rainfall erosivity factor in mountainous catchments.